The Role and Da’wah Strategies of Islamic Religious Counselors in Enhancing the Religiosity of Women at the Al-Hidayah Taklim Assembly - Hidayat, Aceng Nur; Purwandari, Elce; Putri, Depi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study aims to analyze the role and dakwah strategies of Islamic religious counselors in enhancing the religiosity of women in the Al-Hidayah Taklim Assembly. The research focuses on how religious counselors utilize various methods of da'wah to educate, guide, and strengthen the understanding and practice of Islamic teachings among women. A qualitative approach was employed in this study, with data collection techniques including in-depth interviews, observations, and documentation. The main informants in this research were religious counselors, while key and additional informants included taklim assembly participants, administrators, and local religious leaders. The findings reveal that religious counselors play a central role in motivating and guiding women to better understand and practice Islamic teachings through various da'wah methods, such as lectures, memorization, question-and-answer sessions, and personal mentoring. These regular and intensive da'wah strategies have proven to improve the religiosity of women, strengthen social bonds among the congregation, and enhance the quality of their worship. Additionally, support from families, local government, and religious leaders plays a significant role in facilitating the work of religious counselors. However, challenges such as weather conditions and psychological factors of the congregation need to be addressed to further enhance the effectiveness of da'wah. The implications of this study suggest that well-planned and continuous da'wah can have a significant impact on creating a more religious community, especially among the women of the Al-Hidayah Taklim Assembly.